Algorithm of actions in iatrogenic vascular aneurisms - N. Zayniddin; F. Sh. Bakhriddinov; F. S. Ilkhamova (Сибирский научный медицинский журнал, 2020)
Aim of the study was the development of treatment and diagnostic algorithm for iatrogenic vascular aneurysms and their surgical treatment. Material and methods. The paper presents an analysis of the treatment results of 19 patients (15 men – 78.9 % and 4 women – 21.1 %) with iatrogenic vascular damages and their consequences. The method of endovascular complete vascular occlusion was used for the patients treatment. Results. The following methods were used for surgical treatment: vascular ligation – 3 cases, side seam – 6; plastic surgery was performed on the vessels of 4 patients (autovenous, homovenous or synthetic prosthetics) with the use of endovascular full vascular occlusion. The following methods were used after the aneurysm removal: lateral suture – 6 (31.5 %); circular seam – 1 (5.2 %); dressing – 4 (21 %); autovenous shunting – 2 (10.5 %); extraanatomical shunting – 1 (5.2 %); homovenous bypass surgery – 1 (5.2 %); Z-shaped seams – 1 (5.2 %); Palm’s оperation – 1 (5.2 %). The following complications were observed after the operation: vascular thrombosis – 1, arrosive bleeding – 1 patient. There were no forced amputations and deceased patients. In the postoperative period of 16 (84.2 %) patients, wound healing was primary; 3 (15.8 %) healing occurred by secondary intention. Conclusion The proposed diagnostic and treatment algorithm improves the efficiency of surgical treatment of iatrogenic aneurysms by the method of endovascular complete vascular occlusion and obtains good results.